PEMBUATAN ARANG RENDEMEN TINGGI DARI TEMPURUNG KELAPA DENGAN KILN DRUM - Nurmala Hudaya; Hartoyo Hartoyo (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The aim of this research is to improve charcoal kiln and production techniques so that yield and quality can be optimazed with less capital operating cost.The kiln used in this experiment was made from a typical 200 litre oil drum with special design incorporating 12 holes of 13 mm in diameter in different elevations, at the base, 30 cm and 60 cm above the base. A short chimney of 30 cm height at the top with 10 cm in was also installed diameter.This report discusses the experimental procedures including raw material preparation, loading and operation of tedrum kiln. The yield all qualities of the charcoal produced are also discussed in this report. The results of this experiment showed that single Drum Kiln can produce high charcoal yield ranging from 33,8 % to 37,2 % and average of 35,7 %.A comparison of results with survey data shows that the quality of the coconut shell charcoal produced by the drum kiln method. conform favorably with the quality of charcoal being used for production of commercial activated carbon.